A novel droplet digital PCR human mtDNA assay for fecal source tracking. (15th September 2020) - Zhu, Kevin; Suttner, Brittany; Pickering, Amy; Konstantinidis, Konstantinos T.; Brown, Joe
Abstract: Human mitochondrial DNA provides a promising target for fecal source tracking because it is unique and intrinsic to humans. We developed a TaqMan chemistry assay, hCYTB484, targeting the cytochrome b gene of the human mitochondrial genome on a droplet digital PCR (ddPCR) platform and compared the performance of hCYTB484 with the HF183/BacR287 assay, a widely used assay targeting human-associated Bacteroides . For both assays, we defined the analytical limit of detection and analytical lower limit of quantification using frequency of detection and imprecision goals, respectively. We then established these analytical limits using empirical ddPCR data, presenting a novel approach to determining the analytical lower limit of quantification. We evaluated assay sensitivity using individual human feces from US, Bangladesh, and Mozambique and evaluated assay specificity using cow, pig, chicken, and goat samples collected from the US. To compare assay performance across a range of thresholds, we utilized receiver operating characteristic curves. The hCYTB484 marker was detected and quantifiable in 100% of the human feces from the 3 geographical distant regions whereas the HF183/BacR287 marker was detectable and quantifiable in 51% and 31% (respectively) of human feces samples. The hCYTB484 marker also was more specific (97%), having fewer detections in pig, chicken, and goat samples than the HF183/BacR287 marker (80%). The higher performance of the hCYTB484 marker in individual feces from geographically distant regions is desirable in the detection of fecal pollution from sources to which fewer individuals contribute, such as the non-sewered forms of sanitation (e.g. pit latrines and septic tanks) that serve most of Earth's population and carry the highest risk of exposure to fecal-oral pathogens. Graphical abstract: Image 1 Highlights: We developed a novel TaqMan chemistry assay for the ddPCR platform targeting human mtDNA. mtDNA was detected and quantifiable in 100% of human feces samples from the US, Mozambique, and Bangladesh. mtDNA can complement fecal source tracking methods.